History of the United Netherlands from the Death of William the Silent to the Twelve Year's Truce, 1585e - Motley, John Lothrop, 1814-1877 (Salt Lake City, UT : Project Gutenberg, 2004)
"History of the United Netherlands from the Death of William the Silent to the Twelve Year's Truce--1609" by John Lothrop Motley is a historical account exploring the complex and tumultuous events surrounding the Netherlands' struggle for independence from Spanish rule during the late 16th and early 17th centuries. Written in the late 19th century, this book delves into the intricacies of international diplomacy, political alliances, and military conflicts during a critical period in the history of Europe, specifically focusing on the waning influence of Spain in the Netherlands and the political maneuvering of Elizabethan England. Motley's narrative captures the multifaceted dynamics between key figures such as Queen Elizabeth I, English diplomats, and Dutch leaders grappling with the threat of Spanish dominance. The author chronicles the diplomatic missions by Dutch envoys to England, showcasing their appeals for military assistance while they navigate the Queen's cautious and often reluctant approach to aid. Along with the detailed description of events and personalities, including the significant figure of John of Olden-Barneveld, the book reflects on the broader themes of political ambition, religious turmoil, and the quest for national self-determination. Ultimately, it reveals how the fragile alliance between the Dutch provinces and England played a vital role in shaping the outcome of the Thirty Years' War and the subsequent establishment of the Dutch Republic. (This is an automatically generated summary.)
Release date is 2004-01-01
This eBook was produced by David Widger
Keywords: Netherlands -- History -- Eighty Years' War, 1568-1648